Diasporic virginities: Social representations of virginity and identity formation amongst British Arab Muslim women. (March 2015) - Amer, Amena; Howarth, Caroline; Sen, Ragini
This study compares how practising and non-practising British Arab Muslim women position themselves in relation to representations of virginity. Overall, in our qualitative study, we found that representations of culture and religion influenced social practices and social beliefs in different ways: non-practising Muslim women felt bound by culture to remain virgins, while practising Muslim women saw it as a religious obligation but were still governed by culture regarding the consequences of engaging in premarital sex. Interestingly, some practising Muslim participants used Mut'a (a form of temporary 'marriage') to justify premarital sex. This, however, did not diminish the importance of virginity in their understanding and identification as Arab women. In fact, this study found that virginity, for the British Arabs interviewed, embodied a sense of 'Arabness' in British society. Positioning themselves as virgins went beyond simply honour; it was a significant cultural symbol that secured their sense of cultural identity. In fact this cultural identity was often so powerful that it overrode their Islamic identities, prescribing their behaviour even if religion was seen as more 'forgiving'.